IMPLEMENTASI MARKETPLACE TERHADAP PENJUALAN SAYUR SEGAR PADA USAHA DHEA SAYUR - Era Istiawati; Hendri Hermawan; Drajat Setiawan (Prodi Perbankan Syariah UIN Sumatera Utara Medan, 2023)
This research was conducted in Karangtalok Village, Ampelgading District, Pemalang Regency. This research was conducted starting in May 2023. The purpose of this research was to find out how to implement a marketplace on Facebook and how to sell fresh vegetables managed by Dhea Sayur. The research method used is case study research with a qualitative descriptive approach with primary and secondary data through observation, interviews, and documentation. The results achieved in this study are that with the implementation of the Facebook Marketplace, sellers are able to take advantage of digital marketing in reaching various elements so as to make it easier to get consumers and are expected to be able to introduce and improve products in their marketing. Based on the results of the conclusion, sales using the Facebook Marketplace have not resulted in effective marketing in making sales through online shop